Integration of HIV Prevention With Sexual and Reproductive Health Services: Evidence for Contraceptive Options and HIV Outcomes Study Experience of Integrating Oral Pre-exposure HIV Prophylaxis in Family Planning Services in Lusaka, Zambia - Kasaro, Margaret Phiri; Sindano, Ntazana; Chinyama, Manze; Mudenda, Mayaba; Chilaisha, Florence; Price, Joan T.; Chileshe, Modesta (Frontiers in Reproductive Health, 2021)
The WHO guideline on integration of family planning (FP) and pre-exposure HIV prophylaxis (PrEP) to enhance the health of women and adolescent girls is reflected in the Zambia Consolidated Guidelines for Treatment and Prevention of HIV Infection 2020. There is however dearth of data on integration of PrEP and FP in Zambia. We describe the integration of oral PrEP in FP services using the ECHO study experience at Kamwala District Health Centre in Lusaka, Zambia. The provision of oral PrEP at Kamwala started in October 2017, lasting for approximately 11 months and utilized the model where initial processes to offer PrEP were on- site followed by off-site referral to laboratory and PrEP provider services. The characteristics of 658 women who enrolled in ECHO at Kamwala are representative of women accessing FP services in Lusaka. 644 of the enrollees were offered oral PrEP. The proportion of women accepting PrEP was low at 1.08% and the proportion of study visits at which PrEP was requested was also low at 0.57%. Those who accepted PrEP were above 20 years old, married, with at least primary education; sexual behavior and risk comparable to decliners. The ECHO study experience indicates that set up and integration of oral PrEP and FP services is feasible in our setting. However, uptake of PrEP was very low. Possible contributory factors were: 1) Timing of introduction of PrEP mid-way in the study, 2) PrEP being a new intervention, 3) Challenges of autonomy of young women to include a daily pill into their lives and anticipated challenges to adherence because of fear of adverse events, 4) Possible under determined risk due to use of an unvalidated risk assessment tool and assessment by health care provider versus self-assessment and 5) Extra layer of challenges to negotiate due to need for off-site referrals. Following these findings our conclusion is that further research through demonstration projects of integration of oral PrEP and FP may provide solutions to low uptake. This information is critical for scaling up of integration HIV prevention services and sexual and reproductive health (SRH) services.